Adolescent reserve capacity, socioeconomic status and school achievement as predictors of mortality in Finland - a longitudinal study - Paulyn Jean Acacio-Claro; Leena Kristiina Koivusilta; Judith Rafaelita Borja; Arja Hannele Rimpelä (BMC, 2017)
Abstract Background Despite robust evidence on the inverse relationship between socioeconomic status (SES) and mortality, deviations from expected results have been observed likely due to school achievement and psychosocial resources, termed as "reserve capacity." Since adolescence is a critical period in developing sound psychological and behavioural patterns and adolescent markers of SES were seldom used, we determine if family SES in adolescence predicts later mortality. We also study how reserve capacity (perceived health, health-promoting behaviour and social support) and school achievement modify this relationship and reduce the negative effects of low SES. Methods A longitudinal study was designed by linking baseline data on 12 to 18 year-old Finns in 1985-95 (N = 41,833) from the Adolescent Health and Lifestyle Surveys with register data on mortality and SES from Statistics Finland. Average follow-up time was 18.4 years with a total of 770,161 person-years. Cox regression models, stratified by sex, were fitted to determine the effects of variables measured during adolescence: family SES, reserve capacity and school achievement on mortality risk. Results All reserve capacity dimensions significantly predicted mortality in boys. Perceived health and social support predicted that in girls. Adolescents with the lowest school achievement were more than twice at risk of dying compared to those with better school performance. Low SES increased the risk of death in boys (Hazard ratios: 1.6, 95% CI 1.1-2.4) but not in girls. Reserve capacity and school achievement weakened the effects of low SES on boys' risk of death. Conclusions High reserve capacity and good school achievement in adolescence significantly reduce the risk of mortality. In boys, these also mitigate the negative effect of low SES on mortality. These findings underscore the roles of reserve capacity and school achievement during adolescence as likely causal or modifying factors in SES-health inequalities.